2023
DOI: 10.1186/s12955-023-02129-7
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of food choice upon associations between adolescent health-related quality of life and physical activity, social media use and abstinence from alcohol

Abstract: Background Understanding how health-related quality of life (HRQoL) is related to lifestyle factors during adolescence is crucial to effective health promotion. The aim of this analysis was to identify associations between HRQoL and lifestyle and to determine the degree to which they are mediated by food choices in adolescents. Methods The Wellbeing in Schools (NI) survey (N = 1609; 13–14 years) assessed HRQoL using the Kidscreen52. Food choice was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Lower HRQoL on the other hand has been linked to more frequent intake of processed food [14], fast food and sugar-sweetened drinks [15]. There is also evidence that diet mediates the relationships between HRQoL, social media use and physical activity [51]. Given the importance of dietary patterns to HRQoL and health behaviour, this research considers whether dietary patterns at an earlier age are associated with HRQoL later in adolescence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower HRQoL on the other hand has been linked to more frequent intake of processed food [14], fast food and sugar-sweetened drinks [15]. There is also evidence that diet mediates the relationships between HRQoL, social media use and physical activity [51]. Given the importance of dietary patterns to HRQoL and health behaviour, this research considers whether dietary patterns at an earlier age are associated with HRQoL later in adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…A longitudinal study conducted in Norway observed a decrease in HRQoL (Kidscreen10) in both boys and girls aged 11-14 years over three years [19]. Compared to females, adolescent males make less healthy food choices [1,3,16,[20][21][22]51] and consume meat more frequently [20,[23][24].. Given some evidence for gender differences in HRQoL along with consistent evidence for gender differences in dietary practices, boys and girls have been considered separately for the purpose of this analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Misleading claims, poorly labeled advertisements, heavily filtered or edited images, and health advice that has not been fact-checked often dominate social media, leading to distorted perceptions of body image and healthy behaviors. 4,5 An estimated 13% of young adults experience an eating disorder and 15% to 47% participate in disordered eating behaviors by age 20, reporting social media as a source driving these behaviors. 4 The constant comparison to unattainable body standards on social media also contributes to body dissatisfaction, low self-esteem, and increased anxiety and depression levels.…”
mentioning
confidence: 99%
“…Health misinformation exacerbates the adoption of harmful behaviors, including disordered eating (irregular eating behaviors that may or may not be diagnosable as an eating disorder, such as restrictive dieting; rigid eating routines; or use of exercise, food restriction, or purging to compensate for food consumed) among youth. Misleading claims, poorly labeled advertisements, heavily filtered or edited images, and health advice that has not been fact-checked often dominate social media, leading to distorted perceptions of body image and healthy behaviors . An estimated 13% of young adults experience an eating disorder and 15% to 47% participate in disordered eating behaviors by age 20, reporting social media as a source driving these behaviors .…”
mentioning
confidence: 99%
See 1 more Smart Citation